Effects of aflatoxins and fumonisins, alone or in combination, on performance, health, and safety of food products of broiler chickens, and mitigation efficacy of bentonite and fumonisin esterase - Ochieng, P.E.; Croubels, S.; Kemboi, D.; Okoth, S.; Baere, S. de; Cavalier, E.; Kang'ethe, Erastus K.; Faas, J.; Doupovec, B.; Gathumbi, J.; Douny, C.; Scippo, M.-L.; et al. (American Chemical Society, 2023)
The current study evaluated the effects of feeding diets contaminated with aflatoxin B1 (AFB1), fumonisins (FBs), or both on the performance and health of broiler chickens and the safety of their food products as well as the efficacy of bentonite and fumonisin esterase to mitigate the effects of these mycotoxins under conditions representative for sub-Saharan Africa (SSA). Four hundred one-day-old Cobb 500 broiler chickens were randomly assigned to 20 treatments with either a control diet, a diet with moderate AFB1 (60 μg/kg feed) or high AFB1 (220 μg/kg feed), or FBs (17,430 μg FB1+FB2/kg feed), alone or in combination, a diet containing AFB1 (either 60 or 220 μg/kg) and/or FBs (17,430 μg FB1+FB2/kg) and bentonite or fumonisin esterase or both, or a diet with bentonite or fumonisin esterase only. The experimental diets were given to the birds from day 1 to day 35 of age, and the effects of the different treatments on production performance were assessed by feed intake (FI), body weight gain (BWG), and feed conversion ratio (FCR). Possible health effects were evaluated through blood biochemistry, organ weights, mortality, liver gross pathological changes, and vaccine response. Residues of aflatoxins (AFB1, B2, G1, G2, M1 and M2) were determined in plasma, muscle, and liver tissues using validated UHPLC-MS/MS methods. The results obtained indicated that broiler chickens fed high AFB1 alone had poor FCR when compared to a diet with both high AFB1 and FBs (p = 0.0063). Serum total protein and albumin from birds fed FBs only or in combination with moderate or high AFB1 or detoxifiers increased when compared to the control (p < 0.05). Liver gross pathological changes were more pronounced in birds fed contaminated diets when compared to birds fed the control or diets supplemented with mycotoxin detoxifiers. The relative weight of the heart was significantly higher in birds fed high AFB1 and FBs when compared to the control or high AFB1 only diets (p < 0.05), indicating interactions between the mycotoxins. Inclusion of bentonite in AFB1-contaminated diets offered a protective effect on the change in weights of the liver, heart and spleen (p < 0.05). Residues of AFB1 were detected above the limit of quantification (max: 0.12 ± 0.03 μg/kg) in liver samples only, from birds fed a diet with high AFB1 only or with FBs or the detoxifiers. Supplementing bentonite into these AFB1-contaminated diets reduced the levels of the liver AFB1 residues by up to 50%. Bentonite or fumonisin esterase, alone, did not affect the performance and health of broiler chickens. Thus, at the doses tested, both detoxifiers were safe and efficient for use as valid means of counteracting the negative effects of AFB1 and FBs as well as transfer of AFB1 to food products (liver) of broiler chickens.